THE INFLUENCES OF ELLBOS IN SPEAKING ANXIETY AT ELEVENTH GRADE STUDENTS OF SMA KRISTEN RANTEPAO - Defliyanto Oktavian Kambuno; Nehru Pasoloran Pongsapan; Linerda Tulaktondok (Teaching English as a Foreign Language Overseas Journal, 2023)
The objective of this research was to find out What are the influence of ELLBOS in speaking anxiety at the eleventh-grade student of SMA Kristen Rantepao. In carrying out this study, researcher used quantitative methods. The subjects of this study were 24 students grade 11 students of Rantepao Christian High School. Data from this study was collected by using a questionnaire. After the data was collected the researcher then used the SPSS 26 program to analyze. The results of this study show that ELLBOS has an influence on students' speech anxiety, especially on the 3 types of speaking anxiety described in this study. Where in communication apprehension before treatment the average achieved by students only reached 3.22. After the treatment is given, the median score that students achieve is 4.00. In test-anxiety, before doing treatment, the average student only reached 2.98. Then after the researcher gave a treatment the normal number of students reached 4.00. Then fear of negative evaluation The average pre-test value only reached 3.14 before the treatment was given. After the treatment was given, the mean number of students reached 4,026. Where from all types of anxiety can be seen that students become more communicating and very enthusiastic. Students also do not feel afraid to make mistakes when learning is carried out. So it can be concluded that ELLBOS has an influence in students' speaking anxiety